(untitled) (Лучшие интеллектуальные исследования, 2025)
Аннотация: В этой статье рассмотрим несколько удобных способов обучения лексике, которые подходят для школьников и студентов. Изучение лексики в образовательном пространстве дает системный подход в изучении лексических понятий, знакомит обучающихся со словом, как единицей лексики, также со значением слова, создает условия для целенаправленного обогащения словарного запаса обучающихся, формирует коммуникативную компетенцию школьников и студентов. Тут мы рассмотрим как учить учеников и студентов лексику. Abstract: In this article, we will consider several convenient ways of teaching vocabulary that are suitable for schoolchildren and students. Studying vocabulary in the educational space provides a systematic approach to studying lexical concepts, introduces students to the word as a unit of vocabulary, as well as to the meaning of the word, creates conditions for the targeted enrichment of the vocabulary of students, and forms the communicative competence of schoolchildren and students. Here we will consider how to teach pupils and students vocabulary.